(untitled) (Semiárida, 2020)
The series of precipitations 1921-80 for the localities of Guatraché, Santa Rosa and General Pico in the Province of La Pampa, have a secular positive tendency for the annual values and for the most rainy month in every one of these towns. On the contrary in the driest month, the secular tendency is negative. Similar statistical treatment is done in Santa Rosa for every month of the year, finding positive secular tendency values for the warm last six months and a negative tendency for remainder semester.